Energy and cost savings potential of oscillating heat pipes for waste heat recovery ventilation - Govinda Mahajan; Scott M. Thompson; Heejin Cho (Energy Reports, 2017)
The feasibility of using finned oscillating heat pipes (OHPs) for heat exchange between counter-flowing air streams in HVAC air systems (i.e., outdoor and exhaust air flows), along with the associated cost savings in typical North American climates, is investigated. For a prescribed temperature difference and volumetric flow rate of air, rudimentary design parameters for a viable OHP Heat Recovery Ventilator (OHP-HRV) were determined using the ε-NTU (effectiveness-Number of Transfer Unit) method. The two-phase heat transfer within the OHP-HRV is modeled via effective evaporation/condensation heat transfer coefficients, while the latent heat transfer required to initiate OHP operation via boiling and evaporation is also considered. Results suggest that an OHP-HRV can possess a reasonable pressure drop (<200 Pa) and is capable of achieving heat recovery rate >5 kW. The proposed OHP-HRV can possess an effectiveness near 0.5 and can pre-cool/heat HVAC air by >5êC. Potential energy and cost savings associated with using an OHP-HRV were estimated for commercial building envelopes in various regions of the United States. It is found that the proposed OHP-HRV can save more than 2500 annually in cities that have continental climatic conditions, such as Chicago and Denver, and for the selected locations the average yearly cost savings per building is found to be on-the-order of 700. Overall, the OHP-HRV shows potential in effectively reducing energy consumption and the operational cost of air handling units in buildings.
Keywords: 330; Heat recovery ventilator; Oscillating heat pipe; Pulsating heat pipe; Waste heat recovery